2012
DOI: 10.1017/cbo9781139031158
|View full text |Cite
|
Sign up to set email alerts
|

The Cambridge Introduction to Christopher Marlowe

Abstract: Providing a comprehensive survey of Christopher Marlowe's literary career, this Introduction presents an approachable account of the life, works and influence of the groundbreaking Elizabethan dramatist and poet. It includes in-depth discussions of all of Marlowe's plays, stressing what was new and revolutionary about them as well as how they made use of existing dramatic models. Marlowe's poems and translations, sometimes marginalised in discussions of his work, are analysed to emphasise their literary import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…However, there are a few things we need to take into account before discussing this. First of all, research on G Â E interactions is still in its infancy and findings need replication and extension before we can know their full implications (e.g., Duncan and Keller, 2011;Rutter, 2012). Second, to date G Â E results are only applicable at a group level.…”
Section: Disclosure Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are a few things we need to take into account before discussing this. First of all, research on G Â E interactions is still in its infancy and findings need replication and extension before we can know their full implications (e.g., Duncan and Keller, 2011;Rutter, 2012). Second, to date G Â E results are only applicable at a group level.…”
Section: Disclosure Of Resultsmentioning
confidence: 99%
“…In the long run, G Â E research may even help to tailor such interventions to the needs of children and parents with specific constellations of genetic and family risk factors. Specifically, leading scholars suggested that in the long run, dependent on sufficiently replicable, generalizable and explicable G Â E findings, it might become possible to target various genetic subgroups with interventions differing in intensity, duration, and even clinical focus (Rutter, 2012). In this light, findings from recent experimental studies that provided evidence for differential responsivity to interventions based on child genetic-makeup are highly intriguing (for meta-analysis see Van IJzendoorn and Bakermans-Kranenburg, 2015).…”
mentioning
confidence: 99%
“…As Tom Rutter suggests, Marlowe's relative youth when he dies (aged twenty-nine) makes the idea of 'late Marlowe' incongruous. 25 But, at the earlier side of the Marlowe chronology, editors and critics such as Paul Menzer, distinguish between the 'juvenilia' of his translations of Ovid and Lucan, associated with the poet-dramatist's time in Cambridge (though with no evidence to support this dating), and his later more accomplished works. 26 Indeed, the categorization of Dido, Queen of Carthage as juvenilia has been protested vigorously.…”
mentioning
confidence: 99%